Factors determining the adoption of strategies used by smallholder farmers to cope with climate variability in the eastern Free State, South Africa - Myeni, L.; Moeletsi, M.E. (MDPI, 2020)
This study was undertaken to understand the smallholder farmer’s perception of the effects of climate variability, their adaptation strategies to cope with climate variability and factors determining the adoption of their adaptation strategies in the eastern Free State Province of South Africa. Adaptation strategies were grouped into two categories, i.e., traditional adaptation strategies and scientific adaptation strategies. Traditional adaptation strategies consisted of practices that require minimal technical expertise and less external inputs such as changing from crops to livestock, crop diversification, increasing land under production, changing crop type and water harvesting. Scientific adaptation strategies consisted of practices that require additional external inputs, labour, and some level of technical expertise such as changing crop variety, improving soil fertility and soil conservation. Data were collected from 391 smallholder farmers using a structured household questionnaire and were verified through focus group discussion meetings with key informants. Data were analysed using the descriptive statistics, frequency analysis and a binary logistic model. Results indicated that the majority of smallholder farmers perceived that climate change had triggered food-related impacts in the study area and had adopted at least one adaptation strategy. This study showed that awareness and knowledge were the key factors that determined the adoption of traditional adaptation strategies in the study area. The adoption of scientific adaptation strategies was additionally determined by the availability of external financial investments. It is recommended that the promotion of traditional practices should focus on raising awareness of climate change and adaptation strategies while the promotion of scientific practices additionally requires the provision and accessibility of financial institutional support and incentives.